DEVELOPMENT OF THE THERMAL BARRIER COATING FOR HEAT AFFECTED COMPONENTS OF AIRCRAFT GROUND SUPPORT EQUIPMENT - Dovgal, Andrey (Proceedings of National Aviation University (archive), 2014)
Heat protection properties of SiC–Al2O3–ZrO2 components composite material in a result of hightemperature oxidization at temperature close to ceramics melting point have been researched. The evidence offormation on the surface of wear- corrosive-proof three-layered protective scale with the outer layer of fine-grainedfibrous structure of aluminium silicate in thickness of 180 micrometers has been established. Application advisability ofspecified composition material, both as the solid bulk, and as coating deposited for protection of heat bearingcomponents of aircraft ground support equipment